anonymous
  • anonymous
When a number has an exponent of zero, why does it equal 1? Shouldn't it be 0?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
anything to the power of 0 = 1
anonymous
  • anonymous
anything but 0.
anonymous
  • anonymous
\[0^0\neq0\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
if all fails use the calculator
anonymous
  • anonymous
I know it equals 1, but I want to know why.
anonymous
  • anonymous
no because the rule is 0 exponents always equal 1
anonymous
  • anonymous
why do you want to know why
anonymous
  • anonymous
math teacher told our class to find out
anonymous
  • anonymous
I guess you can prove it by stating this : x^y = x^a * x^b (provided that y = a+b) If b = 0, x^b needs to =1, else you'd have x^a * 0 = 0 =/= x^y
anonymous
  • anonymous
so by having x^0 = 1, x^a * 1 = x^a = x^(a+0) = x^y. Makes sense?
anonymous
  • anonymous
can u plug in numbers to that as an example please?
anonymous
  • anonymous
consider a^1 ÷ a^1 = a / a = 1 but as per laws of indices, a / a = a^(1 – 1) = a^0 = 1 consider a^2 ÷ a^2 = a × a / a × a = 1 but as per laws of indices, a^2 / a^2 = a^(2 – 2) = a^0 = 1 or 5^3 ÷ 5^3 = 125 / 125 = 1 and 5^3 ÷ 5^3 = 5^(3 – 3) = 5^0 = 1 this shows that any number with exponent 0 is equal to 1
anonymous
  • anonymous
ah, yes, I much prefer intedralsabiti's proof than mine, a lot simpler
anonymous
  • anonymous
his proof also proves that 0^0 doesn't work because you'd need to divide 0 by 0. 0^2/0^2 is impossible, so 0^(2-2) also is, and finally, 0^0 is impossible as well.
anonymous
  • anonymous
i dont deserve that medal.take it back. It is copy-paste
anonymous
  • anonymous
bah, then it's a medal for google-searching skills ;-) whatever works really
anonymous
  • anonymous
thx :D

Looking for something else?

Not the answer you are looking for? Search for more explanations.